Factors influencing academic participation of undergraduate students - Sari Muthia Silalahi (Journal of Education and Learning (EduLearn), 2020)
This study aims to examine factors influencing aspects such as teacher's personality, student's behavior, environmental which has influence student's affective and cognitive. The data were obtained using methods: interview and questionnaire. The random participant has been chosen for interviewed and population has been used for the questionnaire. There were 1585 participants have filled the questionnaire and 24 students have interviewed. Interview data were recorded and analyzed. The results have processed, it was classified according to study programs following the indicator.  The research finding shows that: factors from lecturers and teaching assistants got 78 - 81%, academic and non-academic facilities got 74.91% - 80.86% and dormitory as living for students got 69.16% which have a big impact on influencing student's affective and cognitive. There were also issues such as teacher's centered-learning, most of students and class situations can often be uncomfortable.